2017
DOI: 10.1016/j.eucr.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Hepatic Metastasis from Prostate Carcinoma

Abstract: Worldwide, prostate cancer is considered the second most common cancer in men. Most common sites for metastatic disease are lymph nodes and bones. However, isolated liver metastasis from prostate cancer is rare. We present a 75 year-old male with prostate adenocarcinoma diagnosed 7 years ago. With rising PSA, he underwent imaging and found to have isolated hepatic metastasis. After left hepatic lobectomy, his PSA dramatically decreased to < 0.01. Physicians should be aware of isolated hepatic metastasis in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Liver metastases typically occur in systemic, late stage, hormone refractory disease [10]. However, there are reports of patients with liver metastases as the first site of metastatic disease and the liver representing the only metastatic site [10, 12, 13]. Especially in this patient collective, early and reliable detection of liver metastases is of high clinical importance for accurate staging and therapy planning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver metastases typically occur in systemic, late stage, hormone refractory disease [10]. However, there are reports of patients with liver metastases as the first site of metastatic disease and the liver representing the only metastatic site [10, 12, 13]. Especially in this patient collective, early and reliable detection of liver metastases is of high clinical importance for accurate staging and therapy planning.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the relatively high background activity of the liver might also affect the visibility of liver metastases in 68 Ga-PSMA-PET [14]. Imaging of hepatic PC metastases in 68 Ga-PSMA-PET has been reported in case reports, but not been systematically researched in a larger cohort of patients [12, 1518].…”
Section: Introductionmentioning
confidence: 99%
“…To date, no established locoregional treatment regimens specifically addressing hepatic involvement in prostatic cancer exist. Wang et al [ 17 ] reported 1 case with isolated liver spread and successful surgical resection of a solitary liver metastasis. Due to the multitude of liver metastases in both lobes, liver surgery was no treatment option in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Liver metastases have high incidence in some cancers (breast [146], colorectal [147], and prostate [148]), and it is also of interest in medical research. Breast cancer liver metastasis animal models are developed through portal vein inoculations [149].…”
Section: Intravenous Inoculationmentioning
confidence: 99%